2018
DOI: 10.1016/j.nicl.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Modulating functional connectivity after stroke with neurofeedback: Effect on motor deficits in a controlled cross-over study

Abstract: Synchronization of neural activity as measured with functional connectivity (FC) is increasingly used to study the neural basis of brain disease and to develop new treatment targets. However, solid evidence for a causal role of FC in disease and therapy is lacking. Here, we manipulated FC of the ipsilesional primary motor cortex in ten chronic human stroke patients through brain-computer interface technology with visual neurofeedback. We conducted a double-blind controlled crossover study to test whether manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 105 publications
0
55
2
Order By: Relevance
“…An enhancement of the FC (node degree) of preserved ipsilesional motor areas with neurofeedback led to a significant increase in motor function. This was not the case in a control condition where patients enhanced FC of a brain area not directly implicated in motor function with neurofeedback (Mottaz et al, 2018). Hence an enhancement of network interactions of specific brain nodes seems to be causally related to reduced motor impairment.…”
Section: Network Plasticity-mentioning
confidence: 77%
See 1 more Smart Citation
“…An enhancement of the FC (node degree) of preserved ipsilesional motor areas with neurofeedback led to a significant increase in motor function. This was not the case in a control condition where patients enhanced FC of a brain area not directly implicated in motor function with neurofeedback (Mottaz et al, 2018). Hence an enhancement of network interactions of specific brain nodes seems to be causally related to reduced motor impairment.…”
Section: Network Plasticity-mentioning
confidence: 77%
“…More recently, it has been shown that healthy subjects and stroke patients can learn to voluntarily modulate specific patterns of FC (Sacchet et al, 2012, Koush et al, 2013, Liew et al, 2016. In particular, neurofeedback training of the node degree at the ipsilesional primary motor cortex was associated with improved motor performance of stroke patients (Mottaz et al, 2015(Mottaz et al, , 2018.…”
Section: Modulation Of Ipsilesional Network Interactionsmentioning
confidence: 99%
“…Therefore, such neuromuscular modulation or neural plasticity induced by training may, at least partially, explain the gait improvement. A previous study suggested that individuals with chronic stroke preserve the capacity to increase synchronization of neural activity between different brain regions as measured by EEG connectivity through neurofeedback training [1]. It has been noted that a challenging, unfamiliar and more difficult task for stroke patients may increase the possibilities for brain activation to stimulate behavioral recovery [3].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that chronic stroke patients maintain the capacity to increase synchronization of neural activity between different brain regions as measured by EEG connectivity. These changes of functional connectivity in the motor cortex through neurofeedback correlate with improvements in motor performance [1]. Previously, we demonstrated that a novel specific training, the turning-based treadmill program, yielded greater improvements in gait speed and temporal symmetry than regular treadmill training for people with chronic stroke [2].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the cortical changes at the network level, we considered functional connectivity (FC) patterns that have been previously shown to be sensitive to BCI-related tasks (24) as well as to learning processes (25).…”
Section: Functional Connectivity and Network Analysismentioning
confidence: 99%